Bring on the health economists: time for a rigorous evaluation of senior participative arts. Issue 1 (2014) - ,
Abstract : Purpose – As our elderly population increases, scheduled to rise by 61 per cent in the next 20 years, a national panic has set in about what to do. Antidepressant use is on the rise, and the figures for loneliness and depression skyrocketing. So far, so normal and so very disheartening. The purpose of this paper is to make a radical plea to change our thinking about how the lives of our senior citizens are lived: bring on the health economists, and let us put some serious funding into studying the effects of participative arts on the lives of older people.Design/methodology/approach – This year the author was awarded a Winston Churchill Fellowship to study participative arts for older people in the USA. The author interviewed Professor Julene Johnson of University of California San Francisco, about "Community of Voices" an ambitious, well‐funded five year programme which is launching 12 one‐year choirs with low income, non‐singers, after which findings will be rigorously tested.Findings – In the USA, proper evaluation of participative arts is being taken seriously as a means of whittling down massive Medicare costs. There is evaluation going on in the UK, but much of it is flawed, usually down to cost. Evaluations generally consist of questionnaires filled in by participants. Findings centre around the psychological arena, rather than physical aspects (balance, hospital visits).Originality/value – It is imperative that one starts thinking about participative arts for seniors in a scientific and serious way. The alternative – roomfuls of elders on antidepressants (the UK's antidepressant use was up 23 per cent between 2010 and 2011) does not bear thinking about.